Dynamic performance of pre-cast prestressed beams – cast in-situ slab composite bridges - Leo, Emmanuel (Department of Civil Engineering, 2023)
Most bridge management systems still rely on visual inspections for condition assessment of bridges; this means that damage in inaccessible parts of the structure such as shear connectors in concrete composite bridges remain undetected until catastrophic failure occurs. Localized non-destructive techniques such as ultrasonic techniques, radar method, impact testing, magnetic based methods and proof load tests are limited to small areas, time consuming and require prior knowledge of the damaged zone. These limitations can be overcome by using dynamics-based techniques. The main objective of this work is to investigate experimentally the effectiveness of dynamics-based techniques in assessing the condition of shear connectors in concrete composite bridges consisting of pre-cast prestressed beams and a cast in-situ slab based on measurements taken from the surface of the accessible deck slab. In this research, shear links of 8mm bars extended from beam to the slab are used to stimulate shear connectors in real bridges. The experimental work involved building five concrete composite beams each with different number of shear connectors. The testing procedure consisted of measuring the dynamic properties in both the undamaged and damaged beams. Damage was introduced by accelerating corrosion to a group of shear connectors near the supports in each composite beam. Push-off test was conducted in order to determine the shear capacity of the shear connectors in both undamaged and damaged state. The modal tests were successfully executed and from the modal analysis results it was observed that a beam with large number of shear connectors produce high frequencies and high amplitudes of frequency response functions (FRFs) compared to the one with less number of shear connectors. After the shear connectors were damaged all beams showed similar results. In the FRFs, the frequency peaks shifted to the left and the peaks amplitudes changed, the natural frequencies generally dropped indicating the existence of damage. In an attempt to locate regions with damaged shear connectors, the Coordinate Modal Assurance Criteria (COMAC), change of flexibility, change of curvature and strain energy method were used. All methods showed positive and negative results. The change of flexibility method showed minimum negative results compared to other methods in locating regions with damaged shear connectors. Generally, Results show that dynamics-based techniques can be used to detect and localize regions with damaged shear connectors in pre-cast prestressed beams - cast in-situ slab composite bridges by only taking vibration measurements from the surface of the accessible deck slab.